Expression of OsSPY and 14-3-3 genes involved in plant height variations of ion-beam-induced KDML 105 rice mutants - Boonrak Phanchaisri (2018)
The culm length of two semidwarf rice mutants (PKOS1, HyKOS1) obtained from low-energy N-ion beam bombardments of dehusked Thai jasmine rice (Oryza sativa L. cv. KDML 105) seeds showed 25.7% and 21.5% height reductions and one spindly rice mutant (TKOS4) showed 21.4% increase in comparison with that of the KDML 105 control. A cDNA-RAPD analysis identified differential gene expression in internode tissues of the rice mutants. Two genes identified from the cDNA-RAPD were OsSPY and 14-3-3, possibly associated with stem height variations of the semidwarf and spindly mutants, respectively. The OsSPY gene encoded the SPY protein which is considered to be a negative regulator of gibberellin (GA). On the other hand, the 14-3-3 encoded a signaling protein which can bind and prevent the RSG (repression of shoot growth) protein function as a transcriptional repressor of the kaurene oxidase (KO) gene in the GA biosynthetic pathway. Expression analysis of OsSPY, 14-3-3, RSG, KO, and SLR1 was confirmed in rice internode tissues during the reproductive stage of the plants by semi-quantitative RT-PCR technique. The expression analysis showed a clear increase of the levels of OsSPY transcripts in PKOS1 and HyKOS1 tissue samples compared to that of the KDML 105 and TKOS4 samples at the age of 50-60 days which were at the ages of internode elongation. The 14-3-3 expression had the highest increase in the TKOS4 samples compared to those in KDML 105, PKOS1 and HyKOS1 samples. The expression analysis of RSG and KO showed an increase in TKOS4 samples compared to that of the KDML 105 and that of the two semidwarf mutants. These results indicate that changes of OsSPY and 14-3-3 expression could affect internode elongation and cause the phenotypic changes of semidwarf and spindly rice mutants, respectively. © 2012.